A Marxist Analysis of Alienation in Poetry by Paiwarin Khao-Ngam - Phongphrom, Kanjanaporn (Journal of Graduate MCU KhonKaen Campus, 2023)
This article offers a Marxist critical analysis of poetry by Paiwarin Khao-Ngam. Two of his poems were selected: 1) Nao Dok Chan (The Winter’s Cold of the Palash Flower) and 2) Khon Baek Khao (The Ones Bearing the Rice). The objective of this study was to characterize alienation as it appears in Khao-Ngam’s poetry. The study found that both poems depict social inequalities between the capitalist and working classes. Alienation among members of the working class in the poems is represented as self-alienation, as well as alienation from products as alienation from labour and from fellow beings. The poems evoke the suffering and adversity that members of the working class, or proletariat, must endure, especially those from Northeast Thailand, who are forced to migrate to the city to sell their labor in order to improve their social status, as agricultural production makes an insufficient living. Those who are unable to climb the social latter and who possess fewer assets relative to others in society will tend to feel deprived, alienated, and worthless. According to Marxist theory, these issues can be attributed to capitalism, as worth in such a system is transferred from the human to the resources controlled by that human. Therefore, people in society must struggle to obtain valuable assets in order to demonstrate their own worth. When the ruling class, entrepreneurs or capitalists, aim to increase profits without considering their fellow humans, conflict among social relationships intensifies in the midst of rising inequalities.